2007
DOI: 10.1126/science.1136401
|View full text |Cite
|
Sign up to set email alerts
|

Species Interactions Reverse Grassland Responses to Changing Climate

Abstract: Predictions of ecological response to climate change are based largely on direct climatic effects on species. We show that, in a California grassland, species interactions strongly influence responses to changing climate, overturning direct climatic effects within 5 years. We manipulated the seasonality and intensity of rainfall over large, replicate plots in accordance with projections of leading climate models and examined responses across several trophic levels. Changes in seasonal water availability had pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

34
722
3
3

Year Published

2011
2011
2019
2019

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 693 publications
(762 citation statements)
references
References 32 publications
34
722
3
3
Order By: Relevance
“…Biotic interactions as modulators of climate change effects have been reported from several AQUASHIFT projects (Burgmer and Hillebrand 2011;Dziallas and Grossart 2012;Gaedke et al 2010;Klauschies et al 2012;Sommer and Lewandowska 2011;Wagner and Benndorf 2007;Wagner et al 2012b) as well as from terrestrial ecosystems (Suttle et al 2007). For two-link food chains, it is easy to predict an increasing disadvantage for the prey, if the predator profits more strongly from warming than the prey.…”
Section: Discussionmentioning
confidence: 99%
“…Biotic interactions as modulators of climate change effects have been reported from several AQUASHIFT projects (Burgmer and Hillebrand 2011;Dziallas and Grossart 2012;Gaedke et al 2010;Klauschies et al 2012;Sommer and Lewandowska 2011;Wagner and Benndorf 2007;Wagner et al 2012b) as well as from terrestrial ecosystems (Suttle et al 2007). For two-link food chains, it is easy to predict an increasing disadvantage for the prey, if the predator profits more strongly from warming than the prey.…”
Section: Discussionmentioning
confidence: 99%
“…We found that in this Mediterranean grassland ecosystem, soil moisture, which is affected by season, depth, heating, and plants, plays a dominant role in mediating the effect of those factors on root litter decomposition, which after two seasons did not differ by depth or by treatment. Therefore, it will be important to complement this study with others that manipulate soil moisture (e.g., Suttle et al 2007;Khalili et al 2016) to better understand how decomposition of plant litter and soil organic matter will respond and feedback to climate change.…”
Section: Discussionmentioning
confidence: 99%
“…More specifically, we hypothesized that the level of species' climatic niche conservatism through phenological changes explains, at least partly, the reported wide variance between species in the extent of range shifts and climatic niche conservatism via range shifts. Failure to track a changing climate during flowering has a detrimental effect, increasing the risk of frost and drought damage [10], reducing competitive ability [11] ( particularly against species that are pre-adapted or more responsive [12]), lowering productivity [13] and disrupting temporal interactions between species [14], although climatic conditions can also affect the fitness of plant species outside the flowering season. Species can maintain climatic niche during flowering under a warming climate by two types of responses: range shift and phenological changes.…”
Section: Introductionmentioning
confidence: 99%